Eksistensi Pasraman NonFormal sebagai Lembaga Pendidikan Hindu di Kabupaten Lombok Barat - Luh Apriani (Jayapangus Press, 2022)
Non-formal Pasraman as a Hindu Education Institution in West Lombok Regency is one of the most appropriate choices for Hindus to learn about the teachings of Hinduism, because non-formal Pasraman does not require a prerequisite certificate and there is no age limit for students because non-formal Pasraman provides education for all ages namely from the age of children, adolescents, adults, to the elderly. As a non-formal educational institution, Pasraman has constraints in its implementation, namely management, finance, teaching resources and students' motivation to study at Pasraman. The purpose of this study is to see the existence of non-formal pasraman as a Hindu educational institution in West Lombok Regency. This study uses a descriptive qualitative research method, which collects data using direct observation techniques and interview techniques, the data source comes from primary data and secondary data, then the data is processed and presented with narrative techniques. The results of this study are that although non-formal pasraman in West Lombok Regency experience some difficulties, they still exist and are even developing, with more and more non-formal pasraman having been officially recognized by the ministry of religion. Until now, the non-formal pasraman in West Lombok Regency has focused more on education for seniors and considering the limited human resources available at the pasraman and the interests of students. The conclusion that can be drawn in this study is that non-formal pasraman in West Lombok Regency are currently experiencing developments along with the public's interest in studying religion, however, pasraman as a non-profit educational institution requires encouragement from the community and government, especially in funding so that the management of pasraman can continue to run smoothly.